Identifying critical factors to adopt E-HRM based cloud computing system for healthcare organizations - Ahmed, Yasir Hamad; Mohd Aboobaider, Burhanuddin; Abd Ghani, Mohd Khanapi; Elzamly, Abdelrafe; Doheir, Mohamed A. S. (Science and Engineering Research Support Society, 2019)
The presence of EHRM issues and challenges have critical influence on the success of cloud systems. The aim of the paper is to identify the critical factors leading to adopt E-HRM based cloud computing system for healthcare organizations.There are four dimensions forEHRM based cloud computing system that include electronic human resource management activities,the level awareness of EHRM and cloud computing, IT and cloud computing infrastructure, and management support system and quality for HRM. The critical EHRM issues and challenges need to be addressed and thereafter need to be managed by usingcontrol methods. As a future work, we will apply quantitative to control EHRM issuesbased cloud computing system. A successful EHRM based cloud computing will greatly improve the probability of systemsuccess in healthcare organizations.